Processo de gestão da educação profissional: o caso da política orçamentária do Instituto Federal Sul-rio-grandense (2008-2016) - Favretto, Juliana (2021)
Throughout its history, vocational education has been shaped by interests that served the political and economic system. Along the way, it has received various names and guidelines, and has also served in vocational training for the underprivileged, in basic education, in secondary education, and finally, with the creation of the Federal Institutes, it began to serve in basic education, higher education, postgraduate studies, research and extension. The proposal to create the Federal Institutes prioritized the construction of a new institutional framework based not only on political and pedagogical changes, but also on structural changes, including in the management model. These changes require managers to open channels for the participation of the school community and civil society in their planning, given the need to implement good public management practices, aimed at optimizing public spending and efficiency in the provision of services offered to society based on its real needs. Therefore, this research aimed, in the Public Policies and Power Relations research line of the Postgraduate Program in History, to carry out an analysis of the management model of public resources in the area of ​​professional education, using as an object of study the budgetary policy implemented by the Instituto Federal Sul-rio-grandense (IFSul), located in the state of Rio Grande do Sul, from 2008 to 2016. To this end, we sought to identify how this policy was structured at IFSul and how the school community and civil society participated in the process. From the analysis, we verified how this process of democratization of the budgetary management of education can influence the optimization of public policies for the area of ​​professional education, in order to correspond both to the desires of students and the needs of the local community. The exploratory research involved a historiographical review of works, legislation and internal documents of IFSul (Institutional Development Plans from 2009 and 2014, Statute, General Regulations, Action Plans from 2009 to 2016, Management Reports from 2008 to 2016, minutes of meetings of the Superior Council from 2010 to 2016) combined with field research, based on oral history references, with thirteen interviews with institutional and civil society representatives on the subject. The field research was submitted and approved by the Ethics Committee of the University of Passo Fundo, in 2018, under Process: CAAE 97759818.5.0000.5342. Through the sources, it was observed that IFSul was the result of the remodeling process of the Federal Center for Technological Education of Pelotas (CEFET-RS), which had a budgetary resource management process, organized through the Board of Directors. This process was changed to adapt to the new legislation and the changes arising from the new organizational format of the Federal Institutes. However, this adaptation, despite having provided greater participation of the school community, did not provide greater external participation in financial and budgetary decisions, since the participation of civil society was only contemplated, as defined by legislation, in the meetings of the Superior Council, a place more for ratification than for discussion of the values ​​and allocation of the Institution's budget.